2018
DOI: 10.24247/ijauerdjun20182
|View full text |Cite
|
Sign up to set email alerts
|

Heat Release Rate, Performance and Vibration Analysis of Diesel Engine Operating with Biodiesel -Triacetin Additive Blend Fuels

Abstract: The diesel fuel experiments were conducted on diesel engine, with coconut oil methyl ester (COME)-Triacetin additive blends as alternative fuels. Reduction of CO 2 , CO, HC, NO, and smoke emissions were achieved successfully with 10% Triacetin and 90% COME blend fuel. Three directions of engine cylinder and on the foundation were measured and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Triacetin, being an antiknock fuel with 10% blend fuel, emanated as the best blend fuel with its contribution to reduce cylinder vibration in the vertical direction. By analyzing in-cylinder pressure data and released heat rate, it is observed that the addition of Triacetin increases the ignition delay and the amount of heat release in the premixed combustion duration, but shortens both the diffusive burning duration and hence total combustion duration [6]. Knocking can be prevented by the addition of additives in biodiesel fuel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triacetin, being an antiknock fuel with 10% blend fuel, emanated as the best blend fuel with its contribution to reduce cylinder vibration in the vertical direction. By analyzing in-cylinder pressure data and released heat rate, it is observed that the addition of Triacetin increases the ignition delay and the amount of heat release in the premixed combustion duration, but shortens both the diffusive burning duration and hence total combustion duration [6]. Knocking can be prevented by the addition of additives in biodiesel fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Knocking can be prevented by the addition of additives in biodiesel fuel. Triacetin additive can be used as an antiknock agent to reduce engine knocking, to improve cold flow and viscosity properties of biodiesel [7]. In case of biodiesel-diesel blends the performance of engine increased appreciably with less BSFC for blend fuel and CO, HC, NOx emissions and smoke density reduces significantly but a slight increase in CO2 as the compression ratio increases [8].…”
Section: Introductionmentioning
confidence: 99%